2020
DOI: 10.1002/chem.201904347
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved Dynamics of Struvite Crystallization: Insights from the Macroscopic to Molecular Scale

Abstract: The crystallization of magnesium ammonium phosphate hexahydrate (struvite) often occurs under conditions of fluid flow, yet the dynamics of struvite growth under these relevant environments has not been previously reported. In this study, we use a microfluidic device to evaluate the anisotropic growth of struvite crystals at variable flow rates and solution supersaturation. We show that bulk crystallization under quiescent conditions yields irreproducible data owing to the propensity of struvite to adopt defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…We recently used in situ AFM to establish that struvite crystal growth follows a classical mechanism, whereby new layers nucleate on crystal surfaces and advance by the incorporation of solute molecules at steps. 50 Indeed, a snapshot of a (101) surface during growth in a supersaturated solution (Figure 6A)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently used in situ AFM to establish that struvite crystal growth follows a classical mechanism, whereby new layers nucleate on crystal surfaces and advance by the incorporation of solute molecules at steps. 50 Indeed, a snapshot of a (101) surface during growth in a supersaturated solution (Figure 6A)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…AFM has proven to be a powerful technique for characterizing the growth of crystal surfaces in the absence and presence of inhibitors. We recently used in situ AFM to establish that struvite crystal growth follows a classical mechanism whereby new layers nucleate on crystal surfaces and advance by the incorporation of solute molecules at steps 50 . Indeed, a snapshot of a (101) surface during growth in supersaturated solution (Figure 6A) shows the presence of layers emanating from the bottom left (outside the frame of imaging) with heights equivalent to a single unit cell (h = 0.58 nm).…”
Section: Microfluidics Analysis Of Crystal Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies, together with recent advances in 4D printing (Sydney Gladman et al, 2016), may enable optimization of the design of ureteral stents by prescribing desired properties. Meanwhile, several studies in microbiology have shown the influence of fluid mechanical characteristics on microbial behavior (Kim, Olympiou, McCoy, Irwin, & Rimer, 2020; Laffite et al, 2016; Salta et al, 2013; Zalewska‐Piatek et al, 2020) especially the correlation between the micro‐scale shear stress field and the mobility or attachment of bacteria (Rusconi & Stocker, 2015; Sherman et al, 2019). These efforts will open new avenues to the study of urinary flows, leading to novel ideas and solutions for various urological symptoms, ultimately contributing to the well‐being of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallization is a ubiquitous phenomenon in natural, biological, and synthetic processes that poses significant problems for pathological or infectious human diseases and scale formation in industrial pipelines and wellbores . Research efforts to curtail the deleterious effects of mineral precipitation are focused on the development of economical, facile routes to inhibit crystallization.…”
Section: Introductionmentioning
confidence: 99%